Transformasi Kajian Syarah Hadis di Indonesia: Studi Literature Review (2014-2023) - Insani, Shafwatul; Wan Mokhtar, Wan Khairul Aiman; Sari, Meysitah (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
The study of hadith sharia in Indonesia has continued to develop in recent years. However, systematic studies of its development are still very limited. This research examines the development of hadith sharah in Indonesia in the period 2015-2023 with the aim of tracing methodological trends, approaches and objects of study in hadith sharah studies. The method used in this research is Systematic Literature Review (SLR) which was used to analyze 22 scientific literature to trace the development of hadith sharia studies. The research results show that in general, in the 2015-2020 period, the study of hadith sharia was dominated by the study of traditional books and figures which were linguistic and theological-normative in nature. Meanwhile, the 2020-2023 period is starting to show openness to new forms of expression such as digital media and locality. There are four methods used in hadith sharia, namely the taḥlili (analytical), ijmālī (global), muqāran (comparative) method. Meanwhile, the developing approach includes linguistic, socio-historical, contextual and interdisciplinary. This study also shows that there has not been a significant transformation in the study of hadith sharah, but there are indications of a change in direction in the understanding and delivery of hadith sharah.